Use of digital applications in the medicament calculation education for nursing - Francisco Gilberto Fernandes Pereira; Joselany Afio Caetano; Natasha Marques Frota; Maguida Gomes da Silva
Objective.To evaluate the influence of the use of digital applications in medicament calculation education for nursing students. Methods. An experimental study was developed with a sample of 100 nursing students, who were divided randomly into two groups (use of the Calculation Medicines - CalcMed application - available free on the Internet, n=50) and control (conventional method of the calculator use and pre-math skills, n=50). Both groups were assessed before and after the application of the teaching strategy through a test with ten specific questions of medicament calculations. Results. The study group showed a mean score of 8.14 versus an average of 5.02 in the control group. The average time of test execution was faster in the study group compared to the control group (15.7 versus 38.9 minutes). Conclusion. The strategy of using this application positively influences learning and enables greater security in the implementation of medicament calculations.